Social Innovation in Latin America: Maintaining and restoring social and natural capital - Calvo, Sara; Morales Pachón, Andrés (Social innovation in Latin America: maintaining and restoring social and natural capital, 2021)
The Latin American continent contains an incredibly rich diversity from which humans derive a range of ecosystem services (e.g. material goods, cultural benefits, climate regulation, etc.) that contribute to livelihoods and well-being. It has become critical to reconcile social and environmental issues in the region to ensure that development is sustainable and aligned with the Sustainable Development Goals. To ensure the sustainable use and management of social and natural capital in the region, business, government, social enterprises and NGOs are engaging in different forms of social innovation that account for social, ecological and environmental values. This requires the integration of social and natural capital into decision-making at all levels. Latin America presents a useful scenario to explore social innovation in relation to social and environmental values and the management of local human and natural resources. This book presents social innovation initiatives that incorporate social and natural capital into decision-making processes in Latin America. This book aims to provide the reader with an insight into the relevance of social innovation for maintaining and restoring social and natural capital in Latin America. Using case studies from Ecuador, Colombia, Peru, Chile and Mexico, this book provides an insight into the interactions between social innovation and social and natural capital in Latin America and will be of interest to researchers, academics and students in the fields of social innovation, management studies, environmental economics and sustainability.
Keywords: Latin America; social innovation; Scopus(2); WOS(2)